Tezepelumab in patients with allergic and eosinophilic asthma - Caminati, Marco; Buhl, Roland; Corren, Jonathan; Hanania, Nicola A.; Kim, Harold; Korn, Stephanie; Lommatzsch, Marek; Martin, Neil; Matucci, Andrea; Nasser, Shuaib M.; Pavord, Ian D.; Domingo, Christian (Allergy, 2024)
Asthma is a heterogeneous disease commonly driven by allergic and/or eosinophilic inflammation, both of which may be present in severe disease. Most approved biologics for severe asthma are indicated for specific phenotypes and target individual downstream type 2 components of the inflammatory cascade. Tezepelumab, a human monoclonal antibody (immunoglobulin G2 lambda), binds specifically to thymic stromal lymphopoietin (TSLP), an epithelial cytokine that initiates and sustains allergic and eosinophilic inflammation in asthma. By blocking TSLP, tezepelumab has demonstrated efficacy across known asthma phenotypes and acts upstream of all current clinically used biomarkers. In a pooled analysis of the phase 2b PATHWAY (NCT02054130) and phase 3 NAVIGATOR (NCT03347279) studies, compared with placebo, tezepelumab reduced the annualized asthma exacerbation rate over 52 weeks by 62% (95% confidence interval [CI]: 53, 70) in patients with perennial aeroallergen sensitization (allergic asthma); by 71% (95% CI: 62, 78) in patients with a baseline blood eosinophil count >= 300 cells/mu L; and by 71% (95% CI: 59, 79) in patients with allergic asthma and a baseline blood eosinophil count >= 300 cells/mu L. This review examines the efficacy and mode of action of tezepelumab in patients with allergic asthma, eosinophilic asthma and coexisting allergic and eosinophilic phenotypes.